2017
DOI: 10.1039/c7tc04699e
|View full text |Cite
|
Sign up to set email alerts
|

Large negative magneto-LC effects induced by racemic dimerization of liquid crystalline nitroxide radicals with a terminal cyano group

Abstract: Large negative magneto-LC effects occur in the LC phase of a racemate of a chiral nitroxide radical with a terminal cyano group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The detailed preparation processo fN *-LCs from E7 is described in the Experimental Section5.T he N*-LCs exhibit liquid crystallinity and typical planar Grandjean textures as shown in Figure 3a nd Figure S4, which can be attributed to both dipolar interactions from polar cyano groups and p-p interactions between binaphthyl moiety( R/S-BINOL-CN) and biphenyl/terphenyl groups of the host E7. [21] The mixtures of cyanobiphenyl and cyanoterphenyl compounds of E7 host can effectively enhance such kind of attraction between the host and the dopant of R/S-BINOL-CN containing dicyano-vinyl group, which can form the spontaneous self-assembly with sufficient compatibility, enough fluidity and chirall iquid crystallinity.A si se vident from Figure 3, there is great difference from the POM textures of nematic LC E7 and the chiral N * -LC of the mixture E7 doped with 1wt% R-BINOL-CN in af lat LC cell. At ypicalp lanar Grandjean texture demonstrates the conformationo fanew N * -LC phase (Figure 3 b), which spontaneously aligns to form ah elicallyt wisted structure.…”
Section: As Shown Inmentioning
confidence: 99%
“…The detailed preparation processo fN *-LCs from E7 is described in the Experimental Section5.T he N*-LCs exhibit liquid crystallinity and typical planar Grandjean textures as shown in Figure 3a nd Figure S4, which can be attributed to both dipolar interactions from polar cyano groups and p-p interactions between binaphthyl moiety( R/S-BINOL-CN) and biphenyl/terphenyl groups of the host E7. [21] The mixtures of cyanobiphenyl and cyanoterphenyl compounds of E7 host can effectively enhance such kind of attraction between the host and the dopant of R/S-BINOL-CN containing dicyano-vinyl group, which can form the spontaneous self-assembly with sufficient compatibility, enough fluidity and chirall iquid crystallinity.A si se vident from Figure 3, there is great difference from the POM textures of nematic LC E7 and the chiral N * -LC of the mixture E7 doped with 1wt% R-BINOL-CN in af lat LC cell. At ypicalp lanar Grandjean texture demonstrates the conformationo fanew N * -LC phase (Figure 3 b), which spontaneously aligns to form ah elicallyt wisted structure.…”
Section: As Shown Inmentioning
confidence: 99%
“…25 and 26 provide new track to investigate the orientational interactions between the LC molecules and the GO flakes in accordance with the role of functional groups. Most recently, Uchida et al 27 . have shown that if cyano (CN) group is present at the terminal position of a LC compound, it causes specific negative magneto−LC effects.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant literature reports, [14] the EPR signals of Cr 3+ can be observed in the magnetic field range 0 G < B < 6000 G. The signals in the green and blue shadows, belong to the isolated Cr 3+ signal in octahedral sites and the Cr 3+ -Cr 3+ electron exchange coupling pair, respectively. The EPR signals of the isolated Cr 3+ can be fitted into two wide peaks by the Voigt function (Figure 3i), [14,17] and with the increase of Ga 3+ ratio, the maximum value of the spectral splitting factor geff changes from 4.991 to 4.061. These results indicate that the Cr 3+ can occupy two isolated octahedral sites in the samples.…”
Section: Photoluminescence Properties and Site Occupationmentioning
confidence: 99%